2008
DOI: 10.1021/jp7104665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Thioredoxin-Catalyzed Disulfide Reduction. Activation of the Buried Thiol and Role of the Variable Active-Site Residues

Abstract: Thioredoxins (Trx) are enzymes with a characteristic CXYC active-site motif that catalyze the reduction of disulfide bonds in other proteins. We have theoretically explored this reaction mechanism, both in the gas phase and in water, using density functional theory. The mechanism of disulfide reduction involves two consecutive thiol-disulfide exchange reactions, that is, nucleophilic substitutions at sulfur (S(N)2@S): first, by one Trx cysteine-thiolate group (Cys-32) at a sulfur atom of the disulfide substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 44 publications
9
55
2
Order By: Relevance
“…These data support the hypothesis that these residues are not involved in the properties of the dithiol active center (33). A second hypothesis involves the thiolate leaving group, which establishes S Ϫ …H-S hydrogen bonds with the thiol group of the buried cysteines (12). However, the mutation of the second cysteine of the substrate shows a dissociation of the intermolecular complex (13).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These data support the hypothesis that these residues are not involved in the properties of the dithiol active center (33). A second hypothesis involves the thiolate leaving group, which establishes S Ϫ …H-S hydrogen bonds with the thiol group of the buried cysteines (12). However, the mutation of the second cysteine of the substrate shows a dissociation of the intermolecular complex (13).…”
Section: Discussionsupporting
confidence: 69%
“…For deprotonation of the C-terminal thiol, one hypothesis involves a conserved aspartate residue (11). Recently, it was suggested that when the N-terminal thiolate of Trx attacks its substrate disulfide to form a mixed disulfide complex, the leaving thiol group deprotonates the thiol of the C-terminal active site of Trx (12). Finally another hypothesis proposes that the cysteine is activated for its nucleophilic attack by hydrogen bonds between this residue and the backbone amide of the active site tryptophan (13).…”
mentioning
confidence: 99%
“…From these aspects, the effect of the hydrogen bond donors in the Cys-X-Y-Cys motif seems to find greater acceptance in academia (39)(40)(41)(42). Earlier theoretical studies using cluster models (43)(44)(45) suggested that thiol-disulfide exchange is an S N 2 reaction, in which a nucleophilic thiolate (S nuc ) linearly attacked a disulfide with concomitant dissociation of the latter. In this reaction, the S nuc and the leaving sulfur (S lg ) are approximately parallel to each other and orthogonal to the central sulfur (S ox ), in such a way that the reactant and product disulfides exhibit a torsion of ∼90°around the S-S bond axis (37,(46)(47)(48).…”
Section: Gsh/gssg Buffer In Catalysis By Hpdimentioning
confidence: 99%
“…From the point of view of the catalytical effects, the relevant issue is presence of two vicinal cysteines in active site [38][39][40] (Fig. 1).…”
Section: Enzymatic Activitymentioning
confidence: 99%